The Essence of the Teacher-Disciple Tradition Today (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Moral and universal values play an important role in the socialization of young people in this rapidly developing period. With the development of society, the attitude of generations to the problems of morality acquires special significance. “Just as each period has its own ideals in matters of ethics it is a natural process that some criteria influence the worldview and goals of people based on changes in people’s lifestyle, attitude towards themselves and society.” Therefore, moral values are expressed by the essence of the national mentality in connection with the norms of humanism of a particular nation. This article talks about the expression of the teacher-student tradition in the work of Alisher Navoi.